2018
DOI: 10.1007/s10549-018-5012-7
|View full text |Cite
|
Sign up to set email alerts
|

A systematic review of interventions to improve adherence to endocrine therapy

Abstract: that few behavioral intervention studies were conducted on improving adherence to ET therapy. Therefore, the purposes of this systematic review were to explore studies that examined the impact of interventions or strategies to improve ET adherence among women with BrCa, and identify studies offering insights for future researchers designing interventions to improve ET adherence. Given the known health disparities of BrCa survivors that may contribute to lack of ET adherence, 18,27,28 we additionally sought to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
74
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 46 publications
(75 citation statements)
references
References 73 publications
0
74
1
Order By: Relevance
“…Findings from this research will help fill a gap in our current understanding of underlying modifiable factors that influence adherence to AHT, particularly among understudied disparate populations [ 4 ]. To our knowledge, no previous study has applied a multi-level intervention approach to improve adherence to AHT [ 39 ]. Applying this approach to the cancer treatment and survivorship phases of the cancer control continuum is novel because most multi-level research in this area focuses on prevention and screening [ 26 , 40 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Findings from this research will help fill a gap in our current understanding of underlying modifiable factors that influence adherence to AHT, particularly among understudied disparate populations [ 4 ]. To our knowledge, no previous study has applied a multi-level intervention approach to improve adherence to AHT [ 39 ]. Applying this approach to the cancer treatment and survivorship phases of the cancer control continuum is novel because most multi-level research in this area focuses on prevention and screening [ 26 , 40 ].…”
Section: Discussionmentioning
confidence: 99%
“…There is a similar pattern within the field of breast cancer research, where there are fewer intervention studies that focus on improving breast cancer treatment outcomes, compared to screening [ 41 , 42 ]. Among the studies that focus on improving adherence to AHT, few have found significant intervention effects [ 39 , 43 - 45 ] or are currently analyzing data [ 46 ].…”
Section: Discussionmentioning
confidence: 99%
“…We conducted a literature review on interventions that improve endocrine therapy adherence, which identified 2 consequential gaps in existing intervention research: use of education only interventions and a lack of cultural adaptations [9][10][11][12][13][14][15][16]. Next, we examined commercially available cancer and medication adherence mobile health (mHealth) apps as a possible option to address these gaps and assist African-American women with endocrine therapy adherence [17][18][19][20][21].…”
Section: Introductionmentioning
confidence: 99%
“…The purpose of this concurrent convergent mixed methods study [28] was to provide further data to guide the development of the proposed culturally sensitive mHealth app, STORY+ for African-American women with breast cancer. Our initial work has been reported [14,[29][30][31][32][33][34]. The aims of this study were to (1) assess the use of smartphones and computers related to health care in African-American women with breast cancer, and (2) identify foundational aspects to support endocrine therapy adherence for incorporation in an mHealth app.…”
Section: Introductionmentioning
confidence: 99%
“…Adherence to OA is an important indicator of therapeutic response 2,3,6,8,9 . Several studies have shown that poor adherence may affect treatment efficacy, toxicity, public health expenditures, patient survival time, and increase mortality risk [1][2][3][5][6][7][8][9][10][11][12] . For women with hormone receptor-positive breast cancer, for example, mortality can reach up to 49% of nonadherents 8 .…”
Section: Introductionmentioning
confidence: 99%